Common and divergent neural correlates of anomia in amnestic and logopenic presentations of Alzheimer's disease. (January 2017) - Leyton, Cristian E.; Hodges, John R.; Piguet, Olivier; Ballard, Kirrie J.
Abstract: The majority of logopenic variant primary progressive aphasia (lv-PPA) cases harbour Alzheimer pathology, suggesting that lv-PPA constitutes an atypical presentation of Alzheimer's disease (AD). However, even if caused by Alzheimer pathology, the clinical manifestations of lv-PPA differ from those observed in the typical or amnestic AD presentation: in lv-PPA, aphasia is the main feature while amnestic AD is characterised by impaired episodic memory. Anomia or impaired naming, however, is present in both AD presentations. Whether these presentations share anatomical and mechanistic processes of anomia has not been fully investigated. Accordingly, we studied naming performance and its relationship with regions of brain atrophy in 23 amnestic AD and 22 lv-PPA cases with presumed underlying Alzheimer pathology. Both AD groups displayed some degree of anomia and impaired word comprehension but these were particularly severe in lv-PPA and accompanied by a range of linguistic deficits, comprising phonological substitutions, superordinate semantic paraphasias and abnormal single-word repetition. Analysis of cortical thickness revealed that anomia was correlated with thinning in left superior temporal gyrus in both groups. In amnestic AD, however, anomia was also associated with thinning in right inferior temporal regions. Single-word comprehension (SWC), by contrast, was associated with cortical thinning involving bilateral fusiform gyri in both groups. These findings suggest that anomia in both amnestic AD and lv-PPA results from the involvement at multiple steps of word processing, in particular, semantic and lexical retrieval; in addition lv-PPA patients display a more marked involvement of phonological processing.